Fruiting and sporulation of inland spruce cone rust (Chrysomyxa pirolata Wint.) on bells wintergreen (Orthilia secunda [L.] House) in relation to environmental factors in Northern Finland - Kaitera, Juha; Tillman-Sutela, Eila
2015